Pengembangan Perangkat Pembelajaran Problem Solving Performance Modelling Pada Materi Relasi Dan Fungsi - Yulistina Lailatul Khasanah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Problem-solving skills are important competencies that students need to possess. However, based on the results of the literature review and findings at the school, students' mathematical problem-solving skills are still considered low. This condition is influenced by teacher-centered learning and the limited availability of instructional materials for teaching problem-solving skills. Therefore, the development of instructional materials that are capable of facilitating the improvement of students' mathematical problem-solving skills is needed. This study aimed to describe the process and outcomes of developing instructional materials based on the Problem Solving Performance Modelling (PSPM) model for the topic of relations and functions. The study employed the Research and Development (R&D) method using Thiagarajan's 4D model, which consists of the define, design, development, and disseminate stages. The developed products included a teaching module, exemplar problems, student worksheets (LKM), and a user guide. The field trial was conducted at SMP Negeri 14 Jember with 25 eighth-grade students. Data were collected using expert validation sheets, readability test sheets, learning implementation observation sheets, student activity observation sheets, user response questionnaires, and a mathematical problem-solving skills test. The results showed that the developed instructional materials met the criteria of validity, practicality, and effectiveness. The validity scores were 3.81 for the teaching module, 3.83 for the exemplar problems, 3.72 for the student worksheets, and 3.83 for the user guide. Practicality was demonstrated by a student response rate of 79.8%, a teacher response rate of 91.6%, student activities within the ideal time allocation, and a learning implementation rate of 100%. Effectiveness was indicated by a classical learning mastery of 92% and an N-Gain effectiveness score of 69%. Based on these findings, the Problem Solving Performance Modelling instructional materials for the topic of relations and functions are recommended as an alternative resource for teachers to facilitate the teaching of mathematical problem-solving skills.
Validasi dan Finalisasi Ratna 4 Agustus 2026
Keywords: learning materials; problem solving performance modelling; relations and functions; problem-solving ability.